2020
DOI: 10.1186/s42269-020-00310-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable management approach for sucking pests control in betel leaf of Bangladesh

Abstract: Background: Betel leaf is the oldest and now highly paid farmer's crop, but the most vulnerable to insect pests, leading to massive yield drops in Bangladesh. For this reason, the experiment was carried out at the Spices Research Centre, Bangladesh, during the period of January 2018 to December 2018 and to assess the effectiveness of the different bio-rational approach against the betel leaf sucking pests. In this study, BARI Paan-3 was used as a test crop. Studies were important that sucking insect pests to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…D-Limonene, known for its strong aroma, is an active ingredient in several pesticide products that can repel RSW. Our ndings align with previous reports indicating that certain bio-pesticides like Fizimite® 10% (Sodium lauryl ether sulfate), Bio clean® 5% SL, Antario® 0.1% (Bacillus thuringiensis), Success® 2.5% SC (Spinosad), and others effectively combat sucking pests in different crops(Hossain et al, 2020;Rashid et al, 2022;Rahman et al, 2023). The incorporation of bio-pesticides signi cantly enhanced pest management programs and proved compatible with various biorational control methods.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…D-Limonene, known for its strong aroma, is an active ingredient in several pesticide products that can repel RSW. Our ndings align with previous reports indicating that certain bio-pesticides like Fizimite® 10% (Sodium lauryl ether sulfate), Bio clean® 5% SL, Antario® 0.1% (Bacillus thuringiensis), Success® 2.5% SC (Spinosad), and others effectively combat sucking pests in different crops(Hossain et al, 2020;Rashid et al, 2022;Rahman et al, 2023). The incorporation of bio-pesticides signi cantly enhanced pest management programs and proved compatible with various biorational control methods.…”
supporting
confidence: 89%
“…Hossain et al, 2020;Rahman et al, 2023). Additionally, a multiple stepwise linear regression procedure was used to estimate the impact of bi-weekly mean values of meteorological factors (temperature, humidity & rainfall) on the number of ies per lea et in different bi-weeks and the form of this linear regression model is:…”
mentioning
confidence: 99%
“…Up to date, a small number of reports have been available on biorational based management of chilli Thrips. Hossain et al [10] have reported that alternate application of Antario and Fizimite were found effective against betel leaf sucking insect pest. Celiz et al [11] have stated that Thrips were successfully controlled by bio-pesticide called Matrine.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the lowest mite population was recorded from the treatment spraying of Kmite, Soil recharge, HNPV and SNPV along with pheromone mass trapping which was statistically similar with the spraying of Fizimite and Biotrin along with the blue sticky trap and pheromone mass trapping (Table 2). Biopesticide such as Fizimite was found effective for managing sucking pest like red mite [10] . After fruit setting, borer insect pests such as Helicoverpa armigera and Spodoptera litura infest chilli fruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation